The Application of Modern Tools in Wood Carving of the Iranian Traditional Imprints in Tehran’s Artists’ Works - Mehdi Emraee; Morteza Afshar; Khashayar Ghazizade (هنر اسلامی, 2019)
Nowadays, with the development of traditional tools and the use of new tools in embossing, artists have been able to provide precision and elegance in the creation of their products, in addition to preserving the traditional and indigenous values ​​embedded in embossing arts. Traditional arts and the necessity of adhering to and observing the artist's traditions have taken an important step in nurturing artists, creating exquisite works and restoring the cultural and national identity of the Iranian society. The present study is based on the role of tools in the development and evolution of contemporary wooden inlaid art while conserving ethnic values; this research is based on a descriptive-analytic method and seeks to study the impact of tools in contemporary inlaid developments. The statistical population was selected based on the wooden inlaid artworks of contemporary Tehran artists. The role of tools in such phenomena is that it can aid with delicacy in creating cutes in wooden inlaid artwork and offer a variety of access to diverse types of wood texture, color and quality, uniformity and elegance in the preparation of wood with different dimensions, transformation in the use of precision connections, alteration in the structure of the products, especially fine works. Furthermore, the use of precision tools in executing inlaid artworks in proportion to the form and elegance of the work and the role of the tools in altering the base of the work are all features of the flourishment of contemporary inlaid art. Correspondingly, such artworks are boldly compared to the masterpiece counterparts in Iranian art history